A New Megastable Chaotic Oscillator with Blinking Oscillation terms. (30th April 2021) - Veeman, Dhinakaran; Natiq, Hayder; Al-Saidi, Nadia M. G.; Rajagopal, Karthikeyan; Jafari, Sajad; Hussain, Iqtadar
Abstract : Recently, megastable systems have grabbed many researchers' interests in the area of nonlinear dynamics and chaotic systems. In this paper, the oscillatory terms' coefficients of the simplest megastable oscillator are forced to blink in time. The forced system can generate an infinitive number of hidden attractors without changing parameters. The behavior of these hidden attractors can be chaotic, tori, and limit cycle. The attractors' topology of the system seems unique and looks like picture frames . Besides, the existence of different coexisting attractors with different kinds of behaviors reflects the system's high sensitivity. Using the sample entropy algorithm, the system's complexity for different initial values is assessed. In addition, the circuit of the introduced forced system is designed, and the possibility of implicating the system with analog elements is investigated.